Sistem Informasi Geografis (SIG) Kebencanaan Online Pada Posko Palang Merah Indonesia (PMI) Kota Serang - Kania, Raden; Asrori, Khasan; Adam Perdana, Cahyo; Rakhmat, Edy; Hidayanti, Nur (Teknik Informatika Fakultas Ilmu Komputer, 2024)
The Indonesian Red Cross in Serang City has a command post that serves as an information center for disaster events in Serang City. The recording of disaster data carried out by the Command Post is usually by entering it into a .doc format, which makes data storage and presentation less effective. The reports are offline, making them difficult to access for people who want to know about disaster events. The above problem is solved by designing a web-based geographic information system application (web GIS) that can record and present disaster event information. The data collection method used in this research is direct observation and documentation to get the right data. The methodology used in designing this system is the waterfall method. This disaster geographic information system facilitates the preparation of disaster event reports containing coordinates and disaster coverage areas.